The chemical treatability of municipal wastewater - Debik, E; Demir, A; Günay, A (INST LEBENSMITTELTECHNOLOGIE ANALYTISCHE CHEMIE, 2000)
The performance of chemical precipitation on soluble and particulate contaminants in the municipal wastewater is investigated by chemical precipitation. For this purpose, jar test studies are performed by adding alum, ferric salts and lime at optimal dosages to the effluent samples collected from Baltalimanl and Yenikapl Preliminary Wastewater Treatment Plants, which are two of the major wastewater treatment plants in Istanbul. Particulate COD removal efficiency is 90% around optimal dosage except for lime, for both of the wastewaters. If lime is used, then the removal efficiency for the particulate COD becomes lower than the other chemicals. Soluble TP removal efficiency is more than 93% for both of the wastewaters, but particulate TP removal efficiency is 60-77% and less than 50% for Yenikapl and Baltalimanl wastewaters, respectively. Particulate TKN removal efficiency was about 80% for both wastewaters. However, the removal efficiency of soluble TKN was lower than 20%.
Keywords: chemical wastewater treatment; jar test; wastewater treatment; WATER TREATMENT; REMOVAL; Environmental Sciences & Ecology